2018
DOI: 10.1016/j.msksp.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The clinical reasoning process in randomized clinical trials with patients with non-specific neck pain is incomplete: A systematic review

Abstract: In the majority of studies (70%) the described clinical reasoning process was incomplete. A very small proportion (6%) had a 'diagnosed cause'. Therefore, a better methodological quality does not necessarily imply a better described clinical reasoning process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 145 publications
1
17
0
1
Order By: Relevance
“…The experts state that pain alone is not an indication for physiotherapy, and that there must be other signs/symptoms present and/ or at least one or more positive diagnostic test to substantiate the indication for physiotherapy. However, the review of Maissan et al (2018) reported that only 16% of the 122 randomized controlled trials (RCTs) had a diagnosed cause, i.e. at least one diagnostic test was used as an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experts state that pain alone is not an indication for physiotherapy, and that there must be other signs/symptoms present and/ or at least one or more positive diagnostic test to substantiate the indication for physiotherapy. However, the review of Maissan et al (2018) reported that only 16% of the 122 randomized controlled trials (RCTs) had a diagnosed cause, i.e. at least one diagnostic test was used as an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we wanted information on the type of measurement instruments being used for diagnostic and/or evaluative purposes. For this purpose, we offered a list with the most frequently used measurement instruments in patients with non-specific neck pain selected from the 122 RCTs included in the review of Maissan et al (2018) We asked the experts which measurement instruments they use and whether they use additional measurement instruments. We also gathered information about the timing of the evaluative tests; i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of RCTs (n = 122) involving patients with nonspecific neck pain, the clinical reasoning process was reportedly incomplete, specifically in the diagnostic aspect of the process, with only 6% of the RCTs including a complete diagnostic process. 71 …”
Section: Discussionmentioning
confidence: 99%
“…In einer aktuellen Untersuchung reklamieren Maissan und Kollegen, dass in den meisten Studien zum Phänomen Nackenschmerz der dort beschriebene Clinical-Reasoning-Prozess unvollständig war, was folglich bedeutet, dass für die klinische Praxis bessere Leitlinien und Instrumente erforderlich sind [46].…”
Section: Der Standard: Kognitionsorientierte Therapie Mit Internem Fokusunclassified